2021
DOI: 10.3390/cancers13184687
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Derived Extracellular Vesicles in Urine as a Novel Biomarker for Gastric Cancer: Integration of Liquid Biopsy and Metagenome Analysis

Abstract: Early detection is crucial for improving the prognosis of gastric cancer, but there are no non-invasive markers for the early diagnosis of gastric cancer in real clinical settings. Recently, bacteria-derived extracellular vesicles (EVs) emerged as new biomarker resources. We aimed to evaluate the microbial composition in gastric cancer using bacteria-derived EVs and to build a diagnostic prediction model for gastric cancer with the metagenome data. Stool, urine, and serum samples were prospectively collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Proteins and metabolites have been investigated for their diagnostic potential for gastric cancer 132‐135 . Moreover, the microbiome and bacterial‐derived EVs have been investigated in stool, urine and serum samples to demonstrate their potential 136 …”
Section: Resultsmentioning
confidence: 99%
“…Proteins and metabolites have been investigated for their diagnostic potential for gastric cancer 132‐135 . Moreover, the microbiome and bacterial‐derived EVs have been investigated in stool, urine and serum samples to demonstrate their potential 136 …”
Section: Resultsmentioning
confidence: 99%
“…Urine was the second most explored liquid biopsy in GC detection over the last decade, with 29 eligible studies included in this systematic review. Similarly to that observed with saliva and stool, most studies were performed in Asian populations: 12 from China, 39–50 five from Japan, 51–55 four from Taiwan, 56–59 three from South Korea, 37,60,61 and one from Iran 62 . The remaining four studies were carried‐out in Canada, 63 European portion of Russia 64,65 and Zambia 66 .…”
Section: Resultsmentioning
confidence: 97%
“…systematic review. Similarly to that observed with saliva and stool, most studies were performed in Asian populations: 12 from China, [39][40][41][42][43][44][45][46][47][48][49][50] five from Japan, [51][52][53][54][55] four from Taiwan, [56][57][58][59] three from South Korea, 37,60,61 and one from Iran. 62 The remaining four studies were carried-out in Canada, 63 European portion of Russia 64,65 and Zambia.…”
Section: Urinementioning
confidence: 99%
“…Several 16S rDNA amplicon studies using serum, urine, feces, and skin-fluid samples have shown significant differences in MEV composition between healthy and patient groups (Table 2 ). The clinical performance of the diagnostic models as evaluated by area under the curve (AUC) analysis using external validation set was 0.97, 1.00, 0.95, 0.93, 0.87, 0.82, 1.00, and 1.00 for asthma 88 , AD 89 , colorectal cancer 90 , BT 82 , hepatocellular carcinoma 91 , gastric cancer 92 , pancreatic cancer 93 , and biliary tract cancer 94 , respectively. Furthermore, diagnostic models were developed to predict the prognosis of hepatic diseases 91 .…”
Section: Microbial Ev Biogenesismentioning
confidence: 99%